On-chip microresonator dispersion engineering via segmented sidewall modulation - Kheyri, Masoud; Zhang, Shuangyou; Bi, Toby; Pal, Arghadeep; Zhang, Hao; Zhang, Yaojing; Alabbadi, Abdullah; Yan, Haochen; Ghosh, Alekhya; Hill, Lewis; Bianucci, Pablo; Butzen, Eduard; et al. (Photonics Research, 2025)
Microresonator dispersion plays a crucial role in shaping the nonlinear dynamics of microcavity solitons. Here, we introduce and validate a method for dispersion engineering through modulating a portion of the inner edge of ring waveguides. We demonstrate that such partial modulation has a broadband effect on the dispersion profile, whereas modulation on the entire resonator’s inner circumference leads to mode splitting primarily affecting one optical mode. The impact of spatial modulation amplitude, period, and number of modulations on the mode splitting profile is also investigated. Through the integration of four modulated sections with different modulation amplitudes and periods, we achieve mode splitting across more than 50 modes over a spectral range exceeding 100 nm in silicon nitride resonators. These results highlight both the simplicity and efficacy of our method in achieving flatter dispersion profiles.
CRIS-Team Scopus Importer:2025-02-07